Pleistocene Coastal Evolution in the Makran Subduction Zone - Normand, Raphaël; Simpson, Guy; Bahroudi, Abbas (Frontiers in Earth Science, 2019)
Along the coast of the Makran subduction zone (SE Iran and SW Pakistan), active uplift combined with efficient erosion and vigorous sediment transport have led to marine terraces with unique morphology and sedimentology. These terraces are characterized by the systematic presence of an extensive 1-10+m thick sandstone layer capping their wave-cut base. Our investigation of thirty-six sedimentary logs of the terrace deposits revealed a general prograding trend from nearshore to beach deposits moving upsection. The presence of a thick marine sedimentary succession above the erosive platform suggests continued creation of accommodation space following carving of the platform by wave-erosion (i.e., erosion of the platform occurred before the peak of the highstand). Deposition of prograding beaches above the platform is interpreted to have occurred during the sea-level stillstand and the start of sea-level fall and was favoured by a high sedimentary supply. While some terraces evolve into a classic staircase morphology, others are found as flat-topped platforms bounded by steep cliffs, isolated within the low-lying coastal plain. We find that this morphological difference results from a contrast in bedrock erodability (resistant sandstone versus soft marl, respectively). The flat-topped isolated marine terraces with marl bedrock share morphological and sedimentological similarities with Holocene crenulated beaches currently developing in low-lying bays between headlands. As indurated beaches are uplifted into headlands, they influence the development of following generations of beaches before being eroded by surficial erosion and wave action. Our study shows that the coastal geomorphology of the Makran coast is dictated by the interaction between tectonics (providing relative sea-level fall and juxtaposing units of different erodability at the same structural level by faulting), differential erosion between hard and soft rock (responsible for the presence of isolated headlands) and coastal sedimentary transport processes (permitting accumulation of extensive beach deposits).